Behavioral Intention: An Overview And Blibliometric Analysis - Raisa Rahma, Deshinta; Hermawan, Agus (Jurnal Etnik: Ekonomi-Teknik, 2023)
The aims of this research is to explore the topic of ‘behavioral intention’. The literature analyzes from 30 articles from Scopus using Publish or Perish during the period 2018-2023, analyze with blibliometric. The outcome of the review indicated 109 authors from co-authorship data and many recent keywords from co-occurrence. This literature review can be used for a guidance to the next researcher regarding behavioral intention and the connection with other keywords that appropriate.